Conversion of a variety of high free fatty acid containing feedstock to biodiesel using solid acid supported catalyst. (1st October 2015) - Bala, Dharshini D.; de Souza, Kimberley; Misra, Mano; Chidambaram, Dev
Abstract: The present study explores the use of silicotungstic acid anchored to mesoporous siliceous support, Korean Institute of Technology-6 (KIT-6), as a catalyst to produce biodiesel. Silicotungstic acid loaded KIT-6 was synthesized and the physicochemical properties were characterized using scanning electron microscopy, surface area and pore size distribution analyzer, Fourier transform infrared spectroscopy, X-ray diffraction, X-ray photoelectron spectroscopy and inductively coupled plasma – optical emission spectroscopy techniques. Efficiency of the silicotungstic acid loaded KIT-6 in the production of biodiesel from a variety of high free fatty acid containing feedstock was then evaluated. The composition of free fatty acids in all the feedstock oils (algae oil, coffee oil, palmitic acid and used cooking oil) and their biodiesel resulting from the feedstock were also analyzed. Compared with other solid acid catalysts, the resulting materials show stable and highly efficient catalytic performance in biodiesel production with the highest conversion reaching 99%. A sample containing 26 wt% of silicotungstic acid supported on KIT-6 was found to be the most active catalyst for esterification at 70 °C whilst stirring constantly, with an alcohol/acid volume ratio of 2 and 1.5 wt% loading catalyst for 3 h. Furthermore, the catalyst was reused for four cycles indicating recyclability of the catalyst. Graphical abstract: Highlights: Silicotungstic acid (STA) was anchored to mesoporous material, KIT-6. STA loaded KIT-6 was found to act as a catalyst for synthesis of biodiesel. The catalyst was found to esterify coffee oil, algae oil, and used cooking oil. The application of the catalyst resulted in >96% conversion to biodiesel. The catalyst was found to be recyclable.